Etiology of bloodstream infection and antibiotic susceptibility pattern of the isolates - Bhandari, Prashubha; Manandhar, Sarita; Shrestha, Basudha; Dulal, Nabeen (Asian Journal of Medical Sciences, 2015)
Background: Bloodstream infection (BSI) is a signifi cant cause of morbidity and mortality. In Nepal, very few studies on BSIs have restricted the understanding of their cause, prevention and treatment. This cross-sectional study was conducted to isolate BSIs causing pathogens and determine their antibiotic susceptibility pattern in patients visiting Kathmandu ModelHospital during December 2012 to May 2013. Materials and Methods: Standard laboratory procedure was used to screen, isolate and identify the bacteria from 1,205 patients. The antibiotic susceptibility pattern (AST) was analyzed by modifi ed Kirby Bauer technique and data were analyzed using SPSS version-16. Results: Out of 1,205 blood samples, 186 (15.4 %) were culture positive. The most common bacteria isolated were: Salmonella spp., Escherichiacoli, Klebsiella pneumoniae and CoNS. Gram-negative bacteria were the predominant causes of BSIs. Salmonella Typhi was isolated in 71 % cases of bloodstream infection followed by Salmonella Paratyphi A in 16 %, Escherichia coli in 5.3 % and Klebsiella pneumonia in 0.5 %. The gram-positive organism responsible for causing BSI was coagulase-negative staphylococcus in 7 % cases. There was no significant association between bacteremia and gender of the patients. During ASTs, Gram-negative bacteria were sensitive to Chloramphenicol with only 0.5 % resistivity. Salmonella Typhi (85.6 % of isolates) showed resistance to Nalidixic acid. Gram-positive bacteria showed 100 % sensitivity towards Chloramphenicol and Gentamicin and were least sensitive to Amoxicillin. Conclusion: Salmonella spp., was major cause of BSIs. Increase in antibiotic resistivity for BSI causing pathogens has necessitated continuous monitoring of the susceptibility of organisms towards antibiotics. Asian Journal of Medical Sciences Vol.7(2) 2015 71-75